Mensuração da energia despendida no jejum e no aporte calórico (MEL) em parturientes - Melo, Célia Regina Maganha E; Peraçoli, José Carlos [UNESP] (FapUNIFESP (SciELO), 2007)
This research aims to measure the energy spending in parturient women of low gestation risk. Participants were selected randomly and submitted to fasting (n=15; Group I) or honey ingestion (n = 15; Group II). Data were collected by means of capillary blood values and heart frequency monitoring. The paired t-test with a 5% significance level and Tukey's method were used in statistical analysis. The results showed that honey ingestion did not promote an overload in the mother's glucose; the lactate response demonstrated that the substrate offered was well used; the cardiorespiratory rate demonstrated good performance for both groups; the total energy spent during labor demonstrated that carbohydrate ingestion exerts significant influence, improving maternal anaerobic performance; the group which remained in fasting presented, immediately after labor, higher levels of lactate, showing the organism's efforts to compensate for the energy spent.
Measuring the energy spent by parturient women in fasting and in ingesting caloric replacement (honey)
Keywords: Blood glucose; Energy metabolism; Honey; Lactic acid; lactic acid; adult; blood; caloric intake; comparative study; delivery; diet restriction; energy metabolism; evaluation; female; glucose blood level; heart rate; honey; human; labor; metabolism; physiology; pregnancy; prospective study; statistical analysis; Adult; Blood Glucose; Data Interpretation, Statistical; Delivery, Obstetric; Energy Intake; Energy Metabolism; Fasting; Female; Heart Rate; Humans; Labor, Obstetric; Lactic Acid; Pregnancy; Prospective Studies